Integrated the Medical Procedure Analyze Seismic Resilience of Healthcare System: A Critical Review from the Resilience of Healthcare System vs. Medical Demand Perspective - Bin Liang; Qian Tao; Wuping Gao; Quanchang Ren; Xinqiang Yao (Advances in Civil Engineering)
The healthcare system is the bearer of treating the wounded and the victims of earthquakes. The functional integrity of the healthcare system is critical to the process of postearthquake medical rescue. Thus, the requirements for seismic resilience of the medical functions of the healthcare systems are increasing. Many studies have applied resilience research to address critical issues in the medical rescue of postearthquake casualties, such as medical diagnosis, emergency surgery, and intensive care. However, systematic construction is still lacking. System resilience is one of the most promising systemic management theories with great potential to address the abovementioned challenges. This article puts forward a scientific concept that system resilience can improve the efficiency of earthquake relief in medical rescue. Firstly, a scientific review of medical demand and medical resilience was conducted, summarizing resilience and resilience of healthcare system concepts. In addition, the postearthquake medical demand was reviewed, and the classification and distribution probability of postearthquake injuries were summarized. Furthermore, by reviewing the postearthquake medical rescue process, the weak points of each medical link were summarized. Combined with the key points in the medical rescue process, the application of resilience studies in the medical system is reviewed, and the progress of medical resilience is illustrated. In summary, combined with medical demand, the article provides some guidance for the deep integration between medical rescue processes and medical resilience and identifies the challenges of system resilience to reduce the waiting time of the injured future medical rescue in the earthquake.